(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2022)
Solanum nigrum is a flowering plant that originated in Eurasia and has now spread to the Americas, Australia, and South Africa. European black nightshade, blackberry nightshade, or simply black nightshade are all names for this plant. Sn is a vital plant in traditional medicine that may be found all over the world. S. Nigrum, an annual to short-lived perennial herb with white or mauve flowers followed by berries, has been shown to have powerful analgesic, antidiarrheal, antibacterial, antioxidant, and cytotoxic effects. Traditional Indian medicine has employed s.nigrum infusions to treat diarrhoea, gastrointestinal disorders, and fever. The plant’s juice is used to treat ulcers and other skin conditions. The fruits are used as a tonic, laxative, and digestive aid.